FY2019 Bhutan Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in Bhutan assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Bhutan perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Bhutan on: (1) their views regarding the general environment in Bhutan; (2) their overall attitudes toward the WBG in Bhutan; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Bhutan; and (4) their perceptions of the WBG’s future role in Bhutan.